Routledge handbook of behavioral economics - Frantz, Roger; Chen, Shu-Heng, 1959-; Dopfer, Kurt; Heukelom, Floris; Mousavi, Shabnam; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2016)
There is no doubt that behavioral economics is becoming a dominant lens through which we think about economics. Behavioral economics is not a single school of thought but representative of a range of approaches, and uniquely, this volume presents an overview of them.
part Part I Scientists in the field of behavioral economics -- chapter 1 The evolution of behavioural economics / Peter E. Earl -- chapter 2 George Katona: a founder of behavioral economics / Richard Curtin -- chapter 3 Ken Boulding: the image as a precursor to framing? / Stefan Kesting -- chapter 4 Harvey Leibenstein: a first generation behavioral economist / Roger Frantz -- chapter 5 Herbert Simon s behavioral economics / Esther-Mirjam Sent -- chapter 6 Reinhard Selten, the dualist / Rosemarie Nagel -- chapter 7 Gerd Gigerenzer and Vernon Smith: ecological rationality of heuristics in psychology and economics / Shabnam Mousavi -- chapter 8 Richard Thaler s behavioral economics / Floris Heukelom -- chapter 9 Daniel Kahneman and the behavioral economics of cognitive mistakes / Floris Heukelom -- chapter 10 George Katona s contributions to the start of behavioral economics / Hamid Hosseini -- r chapter 13 Schumpeter, Kirzner, Knight, Simon, and others: behavioral economics and entrepreneurship / t
Keywords: Economics -- Psychological aspects